Application of Social Networking in Library Services - Kedar, Manohar Baburao; Shewale, Madhukar N (Journal of Advanced Research in Library and Information Science, 2021)
The unprecedented technological advancement of the 21st century, no doubt has impacted on library services globally and also in India. The Social Media hype has gradually crept into the library profession with social sites such as Facebook, MySpace, Flickr, YouTube, Library Thing, etc; it has become evident that our services will need to change to meet the growing needs of our end users. This paper deals with concept of social networking and its application to Academic library services for a pro-active awareness and training to educate the LIS professional and the Teaching Faculty, Students and Research Scholars on the in valuable importance of utilizing social media in academic library services in digital environment.